Does Economic Integration Stimulate Capital Mobility? An Analysis of Four Regional Economic Communities in Africa. - Saten Kumar; Rahul Sen; Sadhana Srivastava (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2014)
It is well known that high levels of regional integration enable portfolio risk diversification and capital mobility. While there have been a number of empirical attempts to verify the presence of capital mobility using the Feldstein-Horioka (FH) approach, none of them to the best of our knowledge have explicitly examined capital mobility changes across regional economic groupings rather than individual countries in Africa, and analyzed sub-samples to compare effects of pre-versus post integration. Filling this gap in the literature, this paper analyzes how some major regional economic integration initiatives, such as SACU (South African Customs Union), UEMOA (West African Economic and Monetary Union), COMESA (Common Market for Eastern and Southern Africa) and ECOWAS (Economic Community of West African States)) have influenced capital mobility in their member countries. To estimate the investment and savings relationship, we use Pedroni's (2004) fully modified ordinary least squares (FMOLS) panel cointegration method, applying to a sample of 25 African countries for which annual data is available from 1960-2009. To assess robustness of our results, we also employ the fixed effects, random effects and Mark and Sul's (2003) dynamic OLS (DOLS) methods. Our findings suggest that international capital mobility has only slightly increased in the African countries due to these agreements.
Keywords: 330; Regional economic integration; Feldstein-Horioka puzzle; Cointegration; International capital mobility